Intra-family relationashipsof the Vietnamese families : (Khoa hoc Xã hội, 2011)
Improving quality of family relationships is one of the important factor determining sustainable development of society and the success of national industrialization, modernization and construction of socialism. This project, as one component of the Strategy, was used in the building of Strategy for building Vietnamese families in the 2011 - 2020 period, envisioning 2030.